Library as a Growing Organism - Viswanathan, T. (Journal of Information and Knowledge, 1992)
The validity of the Fifth law of Library Science i.e., Library is a growing organism is looked into in the context of advancements in modern technology and their impact on libraries. The use of CD-ROMs in place of conventional books is visualised. The problems and prospects of CD-ROMs are explained.